Outcomes of newborns with tracheostomy: single center experience - Tandırcıoğlu, Ümit Ayşe; Doğan, Özge; Günaydın, R Önder; Yiğit, Şule; Çelik, H Tolga (The Turkish Journal of Pediatrics, 2023)
Background. Babies with severe bronchopulmonary dysplasia (BPD) are discharged with the support of a home-type mechanical ventilator, after opening a tracheostomy. In addition, although rare, tracheostomy is required in the neonatal period in congenital airway malformations. Early tracheostomy is appropriate to prevent complications due to prolonged intubation. We aimed to find the appropriate time for tracheostomy by examining the tracheostomy opening and closing times, complications and demographic characteristics of the patients, who were hospitalized and underwent tracheostomy in our neonatal intensive care unit. Methods. This retrospective study involved infants admitted to the neonatal intensive care unit between January 2014 and 2019 and discharged following tracheostomy. Information acquired from hospital data was enrolled. The protocol was registered with ClinicalTrials.gov identifier NCT04497740. Results. Twenty-six neonates with median 27.5 weeks gestational age and birth weight 885 gr were enrolled in the study. The mean opening time for tracheostomy was 54 ± 24 days, and the postmenstrual age (PMA) was 36 ± 3 weeks. The mean time to closure of tracheostomy in newborns with a tracheostomy was 387 ± 164 days. The duration of accidental decannulation developed as an early complication in 8 patients was mean 11 ± 8 days. Aspiration pneumonia in 2, subglottic stenosis in 5, accidental decannulation in 2, suprastomal collapse in 7, tracheocutaneous fistula in 8 and granulation tissue in 2 patients were found to be late complications, which occurred within median 90 days. Conclusions. If there is no evidence that breathing has improved and the patient is still using a mechanical ventilator at high pressures and high oxygen concentration, a tracheostomy placement should be considered within two months.
Keywords: congenital airway malformations; extremely low birth; neonatal tracheostomy; newborn; premature